National Strategic Projects and Compensation Issues in Land Acquisition in Indonesia: A Justice Theory Perspective - Pattra, Lerri; Ismail, Nurhasan; Wibowo, Richo Andi (Jurnal Hukum dan Peradilan, 2025)
The compensation issue is still one of the factors inhibiting development in Indonesia. The government must develop to establish a flourishing society, as required by Pancasila and the Constitution. The government implements National Strategic Projects and initiatives designed to foster growth and equitable development, increase employment opportunities, and enhance community welfare. Limited land control by the government means that the government also needs land owned by the community. When it comes to inland procurement for development, the community whose land rights are impacted by the national strategic project is nearly always unhappy, especially regarding loss compensation. The most complicated and contentious part of taking land for public use is usually the compensation for losses that arise when the government purchases a piece of land. The limited government budget for building infrastructure and restrictions on regulations for using other state finances have caused the government to look for forms and amounts of compensation that can provide a sense of fairness and worth to the community without burdening state finances. Upholding respect for human rights is acknowledged as a form of protection offered by the state to its citizens in Indonesia, a country that upholds the rule of law. This protection extends to situations where the state takes over community land to be used for development in the public interest. The strategies put out to resolve the land acquisition dispute are grounded in the idea of social justice, which is still relevant and evolving in the Indonesian culture of society.